Question
Asked Jan 16, 2019
35 views

6.3x - 4 = 2.6x - 3

check_circle

Expert Answer

Step 1

We have

6.3x - 4 = 2.6x - 3

Adding 3 and subtracting 2.6x on both side, we get

6.3x - 4 + 3 - 2.6x = 0

3.7x -1 = 0

Step 2

Now adding 1 on both side, we get

3.7x = 1

Step 3

Now divided by 3.7 on both side, we get...

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in